Management of Islamic Tourism with Strengthening of Educational Values of Da'wah in Ie Seum Village, Aceh Besar - Sakdiah Sakdiah; Khairul Habibi; Fitri Ramadhani (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2026)
Purpose – This study examines the strengthening of educational values in Islamic tourism management in Gampong Ie Seum, Aceh Besar. Design/methods/approach – The research approach uses a participatory method with data collection through interviews, observation, and documentation. Findings – The results of the study show that tourism management in Gampong Ie Seum has successfully integrated educational da'wah values, including the application of Sharia regulations through qanun gampong (village regulations), strict supervision by village officials, and moral and behavioral guidance for visitors and business actors in accordance with Islamic teachings. The application of honesty and trustworthiness in tourism business transactions and the existence of social supervision strengthen the quality of da'wah. Conclusion – The main obstacles faced include fluctuations in visitor numbers, security issues, limited facilities, and a lack of ongoing training. Research Implication – Important recommendations are given to strengthen governance, infrastructure, and training in order to maintain the sustainability of Islamic tourism-based da'wah.